Liquid jet cooler-based liquid hydrogen fueling and thermostating launch system development - Shakhov, Yurij (Eastern-European Journal of Enterprise Technologies, 2016)
A variant of modernization is examined of the ground-based system for filling and thermostating by liquid hydrogen of fuel tank of superheavy carrier rocket (CR) “Energy” by using, instead of traditional surface heat exchangers, a jet liquid cooler. The filling systems that are in operation at present imply the filling of CR tanks with cryogenic components in the boiling state, which limits the period when a rocket is positioned in the launching pad. But the system that was created in the USSR way back in 1987 made it possible to fill the CR “Energy” fuel tanks with the components of rocket propellant in the supercooled state with subsequent thermostating of tanks. Filling the CR tanks with components in the supercooled state with heightened density provided for an increase in the mass of payload by 5 % and allowed prolonging the period, which would rather be used for eliminating the malfunctions in preparing CR for launch, without returning the components to the filling tanks. They used as heat exchange devices the heat exchanger-recuperators of the “boiling bath” type. In this case, the semiclosed scheme of the cryogenic component circulation was implemented. Using a compact jet liquid cooler as the heat exchange device makes it possible to eliminate bulky heat exchangers, as well as simplify the system through transition to the closed scheme of liquid hydrogen circulation while thermostating the CR fuel tank. Thus, the cryo-component saving is provided for in the process of cooling the structure elements in preparing for the filling. The procedure for calculating the process of thermostating a fuel tank based on the jet liquid cooler was developed for solving the task of modernization of the filling and thermostating system, which allowed us to calculate attainable parameters of the thermostating system and to determine the range of system working ability. The outlet of external heat flows with power to 1 MW is ensured at pressure at the JCL nozzle exit section 10–30 kPa and temperature of “hot” parahydrogen removal from the tank 18–20 K. In particular, the 73 % increase in the operation period of the system during standard system filling with liquid hydrogen or the savings in liquid hydrogen at the estimated time of CR launch might be regarded as the result of using the modernized filling and thermostating system. The technical solutions proposed may be applied when designing new and modernizing those existing systems of storage, cooling and filling with liquid hydrogen of the carrier rockets fuel tanks, including promising objects of heavy and superheavy CRs: SLS and Falkon Heavy (USA), CZ-5 and CZ-9 (C.P.R), Angara 5V (Russian Federation).